2013
DOI: 10.1039/c2tc00110a
|View full text |Cite
|
Sign up to set email alerts
|

A high work function anode interfacial layer via mild temperature thermal decomposition of a C60F36 thin film on ITO

Abstract: A high work function anode interfacial layer has been developed via a mild temperature thermal decomposition of fluorinated fullerene (C 60 F 36 ) on ITO at 120 C. As revealed by in situ ultraviolet photoelectron spectroscopy (UPS) measurements, after the interfacial modification, the ITO electrode work function can be as high as $5.62 eV. It also possesses very good air stability even after the exposure to air for more than one day. The thermal annealing induced carbon-fluorine bond breaking was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It is worth noting that the energy offset between the HOMO of CuPc and Fermi level of O 2 -G is $0.80 eV, whereas it increases to $1.10 eV for the growth of CuPc on pristine graphene. A smaller energy offset between the HOMO of CuPc and Fermi level of anode is benecial for reducing the possible energy loss during the hole extraction process, 47 and hence the enhanced device performance. In addition, it can be found that the IP of CuPc is different for CuPc on pristine graphene ($5.20 eV) and O 2 -G ($4.90 eV) substrate.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the energy offset between the HOMO of CuPc and Fermi level of O 2 -G is $0.80 eV, whereas it increases to $1.10 eV for the growth of CuPc on pristine graphene. A smaller energy offset between the HOMO of CuPc and Fermi level of anode is benecial for reducing the possible energy loss during the hole extraction process, 47 and hence the enhanced device performance. In addition, it can be found that the IP of CuPc is different for CuPc on pristine graphene ($5.20 eV) and O 2 -G ($4.90 eV) substrate.…”
Section: Resultsmentioning
confidence: 99%
“…11a. 26 The Sn 3d peak located at a binding energy at 485.8 eV of base ITO and the Sn 3d peak of the UV-ozone treatment 10% CsF solution shift at 485.4 eV in Fig. 11b.…”
Section: Resultsmentioning
confidence: 93%
“…25,27 A few studies have reported that an ITO surface can be modified using C 60 F 36 to reduce the hole injection barrier and that CsF enhances the work function of the ITO electrode because of the existence of an ultrathin air-plasma-treated alkali fluoride layer. 26,27 The authors reported the hole-only devices using the ITO as the electrodes. They spin-coated CsF films with different concentration on top of ITO electrode and then baked the films.…”
mentioning
confidence: 99%
“…Because of the induced electronic polarization in the molecules surrounding the ionized molecules, the solid films of C 60 , C 60 F 36 , and C 60 F 48 demonstrate even higher EA values of 3.6, 5.2–5.6, and 5.2–5.4 eV, respectively. High EAs, processability via gas and solution phases, as well as the thermal stability of fluorofullerenes enable their application as p-dopants for fabrication of inorganic and organic semiconductors, high-work function electrodes, and hole transport layers. Thin films of C 60 F 36 and C 60 F 48 were shown to capture electrons from the oxidized Si, H-terminated diamond, and indium tin oxide surfaces. C 60 F 36 and C 60 F 48 are effective low-volatile acceptors for p-doping organic semiconductors to increase their hole conductivity. , The organic p–i–n devices containing C 60 F 36 show efficiencies comparable to devices with the commonly used 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane …”
Section: Introductionmentioning
confidence: 99%
“…17−19 High EAs, processability via gas and solution phases, as well as the thermal stability of fluorofullerenes enable their application as p-dopants for fabrication of inorganic and organic semiconductors, highwork function electrodes, and hole transport layers. Thin films of C 60 F 36 and C 60 F 48 were shown to capture electrons from the oxidized Si, 18 H-terminated diamond, 20 and indium tin oxide 21 surfaces. C 60 F 36 and C 60 F 48 are effective low-volatile acceptors for p-doping organic semiconductors to increase their hole conductivity.…”
Section: Introductionmentioning
confidence: 99%